Chemokines and cytokines in immunotherapy of melanoma and other tumors: from biomarkers to therapeutic targets - Reschke, Robin Niklas; Enk, Alexander; Hassel, Jessica C. (International journal of molecular sciences, 2024)
Chemokines and cytokines represent an emerging field of immunotherapy research. They are responsible for the crosstalk and chemoattraction of immune cells and tumor cells. For instance, CXCL9/10/11 chemoattract effector CD8+ T cells to the tumor microenvironment, making an argument for their promising role as biomarkers for a favorable outcome. The cytokine Interleukin-15 (IL-15) can promote the chemokine expression of CXCR3 ligands but also XCL1, contributing to an important DC-T cell interaction. Recruited cytotoxic T cells can be clonally expanded by IL-2. Delivering or inducing these chemokines and cytokines can result in tumor shrinkage and might synergize with immune checkpoint inhibition. In addition, blocking specific chemokine and cytokine receptors such as CCR2, CCR4 or Il-6R can reduce the recruitment of tumor-associated macrophages (TAMs), myeloid-derived suppressor cells (MDSCs) or regulatory T cells (Tregs). Efforts to target these chemokines and cytokines have the potential to personalize cancer immunotherapy further and address patients that are not yet responsive because of immune cell exclusion. Targeting cytokines such as IL-6 and IL-15 is currently being evaluated in clinical trials in combination with immune checkpoint-blocking antibodies for the treatment of metastatic melanoma. The improved overall survival of melanoma patients might outweigh potential risks such as autoimmunity. However, off-target toxicity needs to be elucidated.
Gesehen am 03.02.2025